Pengaruh Lingkungan Keluarga, Pendidikan Kewirausahaan dan Ekspektasi Pendapatan terhadap Minat Berwirausaha Mahasiswa Universitas Dharma Andalas (Studi Kasus Prodi S1 Manajemen Angkatan 2018-2021) - Tara Natalia Eirene Gulo; Mellyna Eka Yan Fitri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Unemployment remains a significant economic and social challenge in Indonesia. One solution to address this issue is to increase entrepreneurial interest among students. This study aims to analyze the influence of family environment, entrepreneurship education, and income expectations on the entrepreneurial interest of undergraduate management students at Dharma Andalas University.This research employs a quantitative approach using a survey method, involving 169 students who have taken the Entrepreneurship and Innovation course. Data analysis was conducted using multiple linear regression. The results indicate that the family environment and entrepreneurship education have a positive and significant impact on students' entrepreneurial interest. In contrast, income expectations have a positive but insignificant influence.These findings suggest that, in addition to formal education, family support plays a crucial role in encouraging students to pursue entrepreneurship. Therefore, universities should enhance practice-based learning methods, and families are expected to provide greater encouragement to help students gain the confidence to start their own businesses.